The Influence of Technology and Accounting Information Systems Development Against The Accountant Profession in Minimarket Padang - Sri Yuli Ayu Putri; Yuli Ardiany; Delori Nancy Meyla (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2020)
Market agencies such as mini-markets require the use of accounting information systems. Mini-markets have thousands of products that are sold to the public in a variety of types to fulfill the needs of the community and reporting sales per day and purchasing goods from suppliers in the form of financial statements needed by management in a hasty manner.Seeing these conditions, one of the important things in managing a business unit is to make decisions using a computerized accounting information system. This research aims to know the effect of partially or simultaneously the technology and accounting information systems development on the accountant profession at the mini-market inPadang. The analytical method used is multiple linear regression analysis. I expect the outputs of this research to be published in the accredited National Journal and IPR publishing. Based on the results of the analysis and discussion of the influence of the Development of Accounting Information Technology and Systems on the Professional Absorption of Accountants, the following conclusions are, the development of technology partially influences the Professional Absorption of Accountants, accounting Information and the system partially has no effect on the Professional Absorption of Accountants.he development of Accounting Information Technology and System simultaneously influences the Professional Absorption of Accountants.